The role of structural common and country-specific shocks in the business cycle dynamics of the G7 countries - Atilim Seymen; Marcus Kappler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The study analyses the business cycles of the G7 countries in a structural vector autoregression(SVAR) framework comprising output, nominal interest rate and inflation. Common and country-specific supply, demand and nominal shocks of each G7 country are identified, and the corresponding shock propagation channels are computed. We establish the statistical properties of the cyclical fluctuations and investigate the role of each structural common and country-specific shock in the cyclical fluctuations of the variables of interest as well as the business cycle co-movement in the G7 group of countries.
Keywords: C32; E32; 330; International Business Cycles; Common and Country-Specific Structural Shocks; Structural Vector Autoregression Models; Konjunktur; Schock; Konjunkturzusammenhang; VAR-Modell; G-7-Staaten